Evaluating the feasibility of ‘InterpreLab’: a technology-assisted tool for interpreting practice in higher education - Wildi Adila; Ikke Pratama; Muhammad Azfa Alfarisi (Erudita: Journal of English Language Teaching, 2026)
The use of technology-assisted tool for interpreting training has been widely used. In early development of interpreting skills, technology can be used to support the in-class limited activities with a more flexible practice. ‘InterpreLab’ emerges as a technology-assisted platform designed to support introductory interpreting training in higher education. This platform can be used as one of the solutions for these critical issues in interpreting pedagogy. This research explores: (1) the feasibility of the ‘InterpreLab’ in interpreting course, and (2) the students’ concerns regarding the use of ‘InterpreLab’ for interpreting practice. This mixed-methods research evaluates learners’ perceptions with the platform’s key features. The findings show that ‘InterpreLab' are generally feasible for supporting the teaching of interpreting. This area is measured in six dimensions, including: interface and visual appeal, usability, content quality, audio and text-to-speech technology, instructional effectiveness, and overall feasibility. Nevertheless, learners also described challenges related to audio and text-to-speech quality issues, navigation and interface limitations, need for feedback, and content availability and variety. The study also highlights the importance of lecturer mediation and curriculum integration in ensuring meaningful adoption of digital tools in interpreting classrooms. These results contribute to ongoing discussions on technological supports in interpreting pedagogy and offer design recommendations for improving ‘InterpreLab’.